The Green Paper on procurement of non-sensitive defense equipment - Joachim Rohde (Stiftung Wissenschaft und Politik (SWP), 2005)
In September 2003 the European Commission published a Green Paper containing its proposals for restricting the blatant abuse of Article 296 of the Treaty of Amsterdam and ensuring that the procurement of civil and dual-use goods and non-sensitive defense equipment by defense ministries is conducted under conditions of intra-community competition as required by the Treaty. The Green Paper does not deal with the procurement of sensitive defense equipment as defined in Article 296. Not least in order to ensure legal certainty, the German government should support both the Green Paper's proposals: an interpretative communication and a new public procurement directive. (SWP-Comments / SWP)
Keywords: 320